RANCANG BANGUN SISTEM PENGENDALIAN LINGKUNGAN PADA TANAMAN MICROGREEN BUNGA MATAHARI DENGAN METODE FUZZY LOGIC - Abrar, Fachri; Nusantoro, Goegoes Dwi; Maulana, Eka (Jurnal Mahasiswa TEUB, 2024)
Microgreens are plants that require little harvesting time and can be grown indoors. One of the plants that can be grown withmicrogreen is sunflowers. However, growing microgreen sunflowers has problems, namely the growth of mold, and long legs.Some of the factors that affect this are temperature, humidity, and light. Microgreens can be grown indoors, but the indoorconditions are not suitable for the needs of microgreens. The average indoor temperature is 27°C, the air humidity is 80%, and itlacks light supply. Meanwhile, the ideal temperature required by sunflower microgreen is 20-25°C and the ideal humidity is 40-60%. With these conditions, an environmental control system for sunflower microgreen is needed. There are two systems made,namely the temperature and humidity control system with fuzzy logic in controlling the fan speed and the lighting system with LEDlights and lighting for 16 hours. Tests conducted show that the DHT22 sensor used has a temperature accuracy of 99.58% andhumidity accuracy of 99.97%. Testing of the entire system shows that the growth box during the day with the control systeminstalled, can reduce the temperature to an average of 23.16% and humidity of 51.63%. While at night the temperature can reach22.7% and humidity reaches 52.48%. This system can reduce the temperature and humidity to be in accordance with the needs ofmicrogreen sunflowers and fuzzy logic control system can improve the temperature drop to be more stable and close to the setpoint, which is 23°C temperature and 50% humidity. Keywords: microgreen, fuzzy logic, control system, growth box